2015
DOI: 10.1038/ncomms9942
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-depleted outer core revealed by sound velocity measurements of liquid iron–carbon alloy

Abstract: The relative abundance of light elements in the Earth's core has long been controversial. Recently, the presence of carbon in the core has been emphasized, because the density and sound velocities of the inner core may be consistent with solid Fe7C3. Here we report the longitudinal wave velocity of liquid Fe84C16 up to 70 GPa based on inelastic X-ray scattering measurements. We find the velocity to be substantially slower than that of solid iron and Fe3C and to be faster than that of liquid iron. The thermodyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
89
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(106 citation statements)
references
References 51 publications
15
89
2
Order By: Relevance
“…Recent works studying the p-wave velocity of molten iron at up to 70 GPa (ref. 35) and estimating the low temperature at the top of the core36 strongly suggest the presence of hydrogen in the core, something to which the present study adds further evidence.…”
Section: Discussionsupporting
confidence: 76%
“…Recent works studying the p-wave velocity of molten iron at up to 70 GPa (ref. 35) and estimating the low temperature at the top of the core36 strongly suggest the presence of hydrogen in the core, something to which the present study adds further evidence.…”
Section: Discussionsupporting
confidence: 76%
“…Extrapolation to higher pressures of our density measurements are quite close to density calculated from sound velocity measurements on liquid Fe‐C alloys in LH‐DAC (Nakajima et al, ) and fall somewhat below the values obtained by molecular dynamics simulations (Badro et al, ) (Figure , right). However, in view of the relatively large extrapolation from our highest pressure point (58 GPa) to the core‐mantle boundary (CMB) pressure (136 GPa), we can consider these two data sets in overall agreement with our experimental results.…”
Section: Resultscontrasting
confidence: 59%
“…(inset) Zoom over the lower‐pressure range. (right) Expanded view around the CMB pressure showing our extrapolated EoS and the comparison with previous studies (Badro et al, ; Ichikawa et al, ; Nakajima et al, ).…”
Section: Resultsmentioning
confidence: 90%
“…During the differentiation into core and mantle, this carbon could partly be dissolved in the core material, leaving a mantle depleted in carbon. This is derived from recent studies that found that the outer core of Earth may contain some carbon at the 1% weight level (Nakajima et al 2015;Wood et al 2013). 6.…”
Section: Carbon Content Of Planetesimalsmentioning
confidence: 99%